2018
DOI: 10.1111/1556-4029.13817
|View full text |Cite
|
Sign up to set email alerts
|

The Forensic Confirmation Bias: A Comparison Between Experts and Novices

Abstract: A large body of research has described the influence of context information on forensic decision-making. In this study, we examined the effect of context information on the search for and selection of traces by students (N = 36) and crime scene investigators (N = 58). Participants investigated an ambiguous mock crime scene and received prior information indicating suicide, a violent death or no information. Participants described their impression of the scene and wrote down which traces they wanted to secure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 26 publications
3
21
0
3
Order By: Relevance
“…The authors of that study go as far to conclude that their findings signal that "great caution against sweeping interpretations based on archaeological context and preconceptions" (13) should be taken. Furthermore, other studies "demonstrate that context information has an impact on the behavior at the crime scene, regardless of experience" (11). Hence, our study is consistent with, and complements, other studies that do use experts, to give a better understanding of the weaknesses and vulnerability to context in decision-making.…”
Section: The Potential Effects Of Initial Exposure To Context At a Crsupporting
confidence: 87%
See 1 more Smart Citation
“…The authors of that study go as far to conclude that their findings signal that "great caution against sweeping interpretations based on archaeological context and preconceptions" (13) should be taken. Furthermore, other studies "demonstrate that context information has an impact on the behavior at the crime scene, regardless of experience" (11). Hence, our study is consistent with, and complements, other studies that do use experts, to give a better understanding of the weaknesses and vulnerability to context in decision-making.…”
Section: The Potential Effects Of Initial Exposure To Context At a Crsupporting
confidence: 87%
“…It is for this reason that we suggested in the paper that "a valuable comparable study would be to see whether similar effects (to those observed in our study) could be found amongst working professional anthropologists" (2). A recent study (11) examined this very issue and found that working experts with experience are not immune to bias, in fact, they were impacted as much as novices.…”
Section: The Potential Effects Of Initial Exposure To Context At a Crsupporting
confidence: 75%
“…Conversely, some have argued that experts' greater reliance on top–down processing, heuristics, and other cognitive shortcuts (e.g., schemas, selective attention, chunking) may actually render them more vulnerable to bias (Chi, 2006; Dror, 2011; Walther, Fiedler, & Nickel, 2003). While there is ample evidence that forensic experts are vulnerable to bias (see Cooper & Meterko, 2019; Kukucka, 2018), only one study has directly compared the biasability of forensic novices and experts: van den Eeden, de Poot, and van Koppen (2019) found that students' and professionals' investigations of a mock death scene were equally impacted by biasing contextual information. Given that contextual (i.e., Level 3) bias has been shown to affect both novices and experts, and evidence lineups have been shown to improve novices' discriminability, it stands to reason that evidence lineups may likewise benefit expert decision‐making.…”
Section: Novice Versus Expert Decision‐makingmentioning
confidence: 99%
“…Однако в отечественной криминалистической и уголовно-процессуальной литературе эти вопросы практически не нашли своего отражения [10]. Основным источником информации о влиянии когнитивных предубеждений и иных факторов на выводы судебных экспертов являются результаты зарубежных исследований, опубликованные в изданиях международных объединений судебных экспертов и в международном журнале по судебной экспертизе Forensic Science International [9,11].…”
Section: вопросы организацииunclassified